Non-destructive testing of composite materials damaged by lightning strike - Lim, Johnson Yong Shen (Nanyang Technological University, 2020)
In the past, Aluminium used to dominate the aerospace industry in the building of aircrafts. However, composites were later introduced and became the dominant materials. These composites are usually made of Fiber-Reinforced Polymers (FRP). In an aircraft, it was important for it to build with sandwiched structures as it has better strength to weight ratio. The sandwiched structure consists of 2 face sheets made of FRP and a honeycomb core glued in between. The honeycomb core can either be made of Nomex or Kevlar, which are largely used in the aerospace industry currently. It is unavoidable when aircrafts are hit by lightning strike when flying under stormy weather conditions. The lightning strike can cause a ruinous effect on the surface of the FRP face sheets such as developing delamination, whereby it will later lose its mechanical properties and experience fatigue. However, even though visible damage can be seen on the face sheets, it is unsure whether the honeycomb core in between them are damaged. This report will study on how the lightning strike will impose detrimental effect externally and internally on the sandwich structures of the aircraft, whereby the face sheets are made of composites. Experiments were done using Non-Destructive Testing such as A-Scan and C-Scan, with the results collected were based on different temperature tested in the experiment. This report also aims to find out the effectiveness of A-Scan and C-Scan on sandwiched structures. A hot air gun was used during the experiment as heat is needed to simulate the lightning strike to heat a region on the face sheets of the sandwiched structure. Findings of the defected region as well as other results would be discussed and presented with images, together with qualitative and quantitative analysis where it is applicable.